(untitled) (Annals of Medical Research, 2023)
Aim: We aimed to investigate the relationship between uric acid, bilirubin, and albumin levels -all of which are natural antioxidants- and Gamma glutamyl transferase (GGT) -one of the components that contribute to maternal oxidative stress- and birth weight of newborns. Materials and Methods: One hundred twenty-six pregnant women aged between 18-40 years and their babies were included in this retrospective cohort study. Uric acid, GGT, bilirubin levels, age, body mass index (BMI), gravida and parity, number of living children, gestational week, and fetal birth weight were reviewed. Results: The mean age of women was 30.62±5.62. There was a positive correlation between birth weight and albumin (r:0.222, p<0.01), serum uric acid levels (r: 0.292, p<0.01), total bilirubin levels (r:0.261, p<0.01) and a negative correlation between birth weight and GGT (r:-0.311, p<0.01). Conclusion: Natural antioxidants are positively associated with the birth weight of infants, while natural oxidant is negatively related. Oxidative stress should also be considered in pregnant women who are expected to give birth at healthy and normal weight.